Detection of Bioavailable Tetracycline Using Whole-Cell Biosensor Bacteria From Fish Ponds In Patuakhali Sadar, Bangladesh (Research in Agriculture Livestock and Fisheries, 2025)
Aquaculture has widely and successfully used antibiotics due to its rapid expansion. The large-scale use of a wide range of antibiotics, including those that are not biodegradable, ensures their prolonged presence in the aquatic environment. One common class of antibiotics is tetracycline, which is widely used in aquaculture operations to treat diseases. The goal of this study was to detect the concentrations of bioavailable tetracycline from fish ponds in Patuakhali Sadar, Bangladesh. Water samples were collected from 50 fish ponds over 6 months, from February 2024 to July 2024. A whole-cell biosensor, utilizing the biosensor bacterium E. coli K12 pTetLux1, was employed to measure tetracycline concentrations. A luminometer was used to measure Relative Light Units (RLU) to quantify the initial reaction. For both standard solutions and water samples, IC (Induction Coefficient) values were determined, and an identical standard curve was created. Subsequently, the concentration of tetracycline in the water samples was determined by entering their individual IC values into the formula obtained from the standard curve. Antibiotics were indiscriminately used in all the ponds when fish became diseased. Among the 50 sampled ponds, 15 ponds were found below the detection level, and 35 ponds were found to contain tetracycline concentrations within the detection level. The highest concentration, 3036.57 µg/l, was found in a pond of Notun Bazar. The measured tetracycline concentrations ranged from 152.95 to 3036.57 µg/l, indicating the presence of bioavailable tetracycline in different ponds of Patuakhali Sadar, Bangladesh. To fully understand the effects of using antibiotics in aquaculture, more investigation is required.Res. Agric. Livest. Fish. Vol. 12, No. 2, August 2025: 319-332